Trends in socioeconomic inequality of periodontal health status among Dutch adults: a repeated cross-sectional analysis over two decades - An Li; Jan Hendrik Vermaire; Yuntao Chen; Luc W. M. van der Sluis; Renske Z. Thomas; Geerten-Has E. Tjakkes; Annemarie A. Schuller (BMC, 2021)
Abstract Background Studies exclusively focusing on trends in socioeconomic inequality of oral health status in industrialized countries are relatively sparse. This study aimed to assess possible differences in oral hygiene and periodontal status among people of different socioeconomic status (SES) in the Netherlands over two decades. Methods A repeated cross-sectional analysis of 3083 participants aged 25-54 years was conducted on the Dutch National Oral Health Surveys of 1995, 2002, 2007, and 2013. Plaque-free was defined according to the Simplified Oral Hygiene Index (OHI-S = 0). Periodontal status was classified in two different ways, either periodontal health/disease (probing pocket depth index [PDI] = 0/ ≥ 1) or with/without deep pockets (PDI = 2). We used the regression-based absolute and relative effect index to measure the absolute and relative socioeconomic inequalities. Multivariable logistic regressions were used to explore temporal trends in oral hygiene and periodontal status by low- and high-SES groups. Results Age-standardized percentages of individuals with plaque-free increased in the whole population from 1995 to 2013 (12.7% [95% CI 10.5-14.9] to 28.1% [24.8-31.5]). Plaque-free showed significant socioeconomic differences in absolute and relative inequalities in 2007 and 2013. Between 1995 and 2013, age-standardized percentage of periodontal health increased (from 51.4% [48.1-54.7] to 60.6% [57.0-64.1]). The significant absolute inequalities for periodontal health were seen in 2002 and 2013. The relative scale presented a similar pattern. Regarding deep pockets, there was little difference in the age-standardized overall prevalence in 1995 versus 2013 (from 6.5% [4.9-8.2] to 5.4% [3.7-7.0]). The significant absolute and relative inequalities in deep pockets prevalence were found in 1995. Yet, all interaction terms between survey year and SES did not reach significance (plaque-free: P = .198; periodontal health: P = .490; deep pockets: P = .678). Conclusions Socioeconomic inequalities in oral hygiene and periodontal status were present in the Netherlands in the last two decades.